2003
DOI: 10.1038/sj.ijo.0802224
|View full text |Cite
|
Sign up to set email alerts
|

Greater prevalence of iron deficiency in overweight and obese children and adolescents

Abstract: OBJECTIVE: To assess whether overweight children and adolescents, who often have poor dietary habits, are at increased risk of iron deficiency (ID). METHODS:The study sample included 321 children and adolescents followed in two endocrine centers in Israel between 1999 and 2001. The subjects were divided into three groups on the basis of body mass index (BMI) for age and gender as follows: group 1FBMI below 85th percentile (normal weight); group 2FBMI above 85th, but below 97th percentile (overweight); and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
210
6
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(249 citation statements)
references
References 9 publications
21
210
6
12
Order By: Relevance
“…This is consistent with previous studies in children in industrialized countries [13][14][15][16][17][18] reporting an inverse relationship between iron status and adiposity, For example, in the NHANES III sample of 9698 older US children, where 14% were at risk for overweight, 10% were overweight and 3% were iron deficient, those at risk for overweight and who were overweight were twice as likely to be iron deficient compared to those not overweight. 17 Our data demonstrate this same relationship exists in children in transition countries with higher rates of iron deficiency and lower rates of adiposity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous studies in children in industrialized countries [13][14][15][16][17][18] reporting an inverse relationship between iron status and adiposity, For example, in the NHANES III sample of 9698 older US children, where 14% were at risk for overweight, 10% were overweight and 3% were iron deficient, those at risk for overweight and who were overweight were twice as likely to be iron deficient compared to those not overweight. 17 Our data demonstrate this same relationship exists in children in transition countries with higher rates of iron deficiency and lower rates of adiposity.…”
Section: Discussionsupporting
confidence: 91%
“…11 In many lower income countries, the prevalence of overweight is increasing at 2-4 times the rate of the industrialized world. 12 Studies in industrialized countries have consistently found higher rates of iron deficiency in overweight children [13][14][15][16][17][18] and adults. [19][20][21][22][23] Although the mechanism is unclear, this may be due to lower iron intakes and/or increased iron requirements in overweight individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Among the proposed causes are deficient iron intake from an iron poor diet, 2 and deficient iron stores owing to greater iron requirements in obese adults because of their larger blood volume. 3,9,10 The relationship between serum iron and dietary iron intake among obese adults has not been previously examined in large studies. Also, since obesity is considered a chronic inflammatory state, 11 inflammatory-mediated sequestration of iron in the reticuloendothelial system, with resultant hypoferremia despite adequate or even increased iron stores could play a role in the hypoferremia of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…First studies on Fe status in obese subjects showed a high prevalence of deficiency [14,19]; however, Fe status assessment only relied on plasma Fe. The measurement of tissue storage parameters of Fe gives far lower values [24].…”
Section: Iron and Obesity: Protective Effect Of Milk Productsmentioning
confidence: 99%